IMPLEMENTASI KURIKULUM 2013 DALAM PEMBELAJARAN BAHASA INDONESIA DI DALAM DAN LUAR NEGERI (STUDI KASUS PEMBELAJARAN TEKS BIOGRAFI DI SMA NEGERI 1 SURAKARTA DAN SEKOLAH INDONESIA SINGAPURA) - Sholihah, Mutiatus; Saddhono, Kundharu; Anindyarini, Atikah (Basastra: Jurnal Bahasa, Sastra, dan Pengajarannya, 2018)
This research aims to explain: (1) preparation, implementation and assessment of learning, (2) problems encountered in the learning process, and (3) efforts made to overcome problems in the Indonesian Language learning process with Curriculum 2013 in the Class X in SMA N 1 Surakarta and Sekolah Indonesia Singapura.This research is a case study research. Samples in this research are the students of class X IPA III, and X IPA I SMA Negeri 1 Surakarta and students of class X IPA and X IPS Sekolah Indonesia Singapura.The sampling technique is purposive sampling.Technique of data collecting done by observation, interview, and document analysis.Data analysis technique is an interactive analysis model.The result of this research are description about: (1) lesson planning, (2) lesson implementation is not in accordance yet with RPP previously written by the teacher, (3) the assessment of learning has adopted an authentic approach according to Permendikbud Number 23 of 2016, (4) the problems faced are the inadequacy of the RPP with the latest regulation, limited learning resources, limited time and place, limited facilities, limited educators, difficulties in understanding and remembering material presented by teachers, limited knowledge and readiness of teachers, low understanding of Curriculum 2013 to student, and low student learning motivation, (5) the efforts undertaken are the school and teachers trying to follow the development related to the Curriculum 2013.